Physical and Psychological Effects of Bariatric Surgery on Obese Adolescents: A Review - Roberts, Cherie A. (Frontiers in Pediatrics, 2021)
The worldwide obesity crisis is not isolated to adults; rather, obesity in adolescents has reached epidemic levels as well. Bariatric surgery continues to be one of the most effective treatments for obesity, both in adults and adolescents, with new evidence continually emerging; however, research surrounding outcomes of these procedures in younger patients is limited in comparison with data available for adults. Further, it is important to examine psychological aspects of obesity in adolescents, as well as effects of surgery on mental health endpoints. Conditions such as anxiety, depression, anger, and disruptive behavior show increased prevalence among obese adolescents, but minimal research exists to examine changes in such conditions following bariatric surgery. Additionally, there is growing evidence of a bidirectional relationship between sleep (quality; disorders) and the development of obesity, and the effects of this relationship are particularly pronounced in the vulnerable adolescent population. This review aims to compile and discuss the results of literature within the last seven years with regard to overall efficacy of bariatric surgery in adolescent patients in terms of weight and body mass index (BMI) reduction, hormonal changes, and co-morbidity resolution, as well as data surrounding sleep and psychological outcomes. Race, ethnicity, and socioeconomic status were also examined. From this review, we conclude that current research supports bariatric surgery in adolescents as an effective method of treatment for obesity and related co-morbidities; however, minimal long-term data exists to adequately assess efficacy and trends into adulthood. These areas are ripe for future study.